What motivates customers to help restaurants during a widespread crisis?: exploration of consumer behaviors during COVID-19 pandemic - Sarwono, Inneke (Kansas State University, 2023)
In 2020, the restaurant industry was greatly impacted by a widespread crisis, the COVID-19 pandemic. Many restaurants permanently closed their businesses or faced significant challenges to survive. Acknowledging these challenges, some customers reported feeling the urge to help, such as leaving larger tips or visiting the restaurant more frequently. While this anecdotal evidence showed various customers’ helping behaviors, the empirical evidence is still lacking in the restaurant context. Therefore, the purpose of this research was to explore restaurant customers’ helping behaviors and develop and evaluate a conceptual framework. A mixed-methods design consisting of qualitative and quantitative phases was employed to accomplish the purposes of this study. First, a qualitative study (Phase I) using semi-structured interviews was used to discover the different types of helping behaviors including customers’ motives to help restaurants during the pandemic. The findings of this study and in-depth literature review were used to design a conceptual model which later was tested using a structural equation modeling in Phase II. In Phase I, a total of 16 interview participants were selected based on their responses prior to screening questions indicated helping restaurants during the COVID-19 pandemic. All audio interviews were transcribed verbatim and analyzed using thematic analysis. Caring for others and community belongingness and involvement were the main themes identified as the important motivating factors to help restaurants. Moreover, customers developed empathy towards restaurants as they shared good experiences during their past restaurant visits. However, some customers revealed the importance of receiving benefits from transactions with restaurants, such as convenience or value. These underlying motivating factors revealed the existence of both communal and exchange relationships. Based on findings, a conceptual framework was developed for further evaluation. In Phase II, 576 restaurant customers across U.S. provided usable data for testing the conceptual framework. The results showed that the communal relationship was significant in predicting empathic concern ([beta] = .88, p < .001), while the exchange relationship was not significant in predicting empathic concern ([beta] = -.04, p > .01). Furthermore, the result also suggested that not all helping behaviors originated by empathic concerns. Empathic concern was significant in predicting the two factors of helping behaviors related to customer participation behavior and customer citizenship behavior ([beta] = .4, p < .001 and [beta] = .81, p < .001 respectively), but it was not significant in predicting helping behaviors related to customer opportunistic behavior ([beta] = .06, p > .001). Nevertheless, the direct path from a sense of community to all factors of restaurant customer helping behaviors was significant ([beta]customer opportunistic behavior= .75, p < .001; [beta]customer participation behavior = .67, p < .001; [beta]customer citizenship behavior = .52, p < .001), confirming the importance of the sense of community for restaurant customer’s helping behaviors. These findings ultimately provided a theoretical and empirical basis for restaurant customers’ helping behaviors. The results also offered restaurateurs a future reference that might be useful in overcoming crises when running businesses.
Keywords: Restaurant customers’ helping behavior; Exchange relationship; Communal relationship; Empathy; Community